Production of Butanoic Acid from a Mixture of Sago and Molasses via Fermentation Process Using Clostridium acetobutylicum - Echa Raniaputri Ameliya; Abdul Fattaah Naufal Riano; Mutasim Bilah (G-Tech: Jurnal Teknologi Terapan, 2025)
Butanoic acid is a short-chain volatile fatty acid with wide applications in the chemical, pharmaceutical, and energy sectors. Conventional production of butanoic acid relies on petrochemical synthesis, which raises sustainability concerns. This research aims to produce butanoic acid through microbial fermentation using Clostridium acetobutylicum, a bacterium known for its dual-phase metabolic capability. A mixture of sago starch hydrolysate and sugarcane molasses was used as the carbon source. The study investigated the effect of different substrate ratios (1:3 to 3:1) and fermentation times (24 to 120 hours) on butanoic acid production. Hydrolysis of sago was conducted enzymatically using alpha-amylase, followed by anaerobic fermentation. Analysis using GC-MS revealed that the substrate ratio significantly influenced acid production. The 3:1 sago-to-molasses ratio produced the highest butanoic acid concentration (22.97%) after 120 hours, with no indication of a metabolic shift to solventogenesis. Conversely, the 1:1 ratio reached its peak at 17.89% in just 24 hours, followed by a rapid decline, indicating an early phase shift. These results demonstrate the importance of substrate composition in optimizing acidogenic activity and delaying solventogenesis. The findings support the potential of renewable biomass mixtures for sustainable biochemical production.